2019
DOI: 10.3390/su11102938
|View full text |Cite
|
Sign up to set email alerts
|

Asphalt Pavement Acoustic Performance Model

Abstract: Low-noise pavements are used as an effective method of traffic noise mitigation. Low-noise pavements reduce the noise that arises due to interactions between tires and road surfaces (tire/road) via the implementation of three main components: low pavement roughness, negative pavement texture, and a high pavement air-void content. The tire/road noise reduction capabilities of the wearing layer vary depending on the aggregate type, gradation, bitumen and air-void content, and density. Consequently, the demand fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…The impacts of noise on human health have been the focus of attention for many years; some reviews can be found in [109][110][111][112][113][114][115][116]. Infrastructures and mitigation methods were studied, among others, in [117][118][119][120][121][122][123][124][125][126][127][128]. Finally, the reduction of noise produced by engines has been studied in [129][130][131][132][133][134][135][136][137].…”
Section: Aircraftmentioning
confidence: 99%
“…The impacts of noise on human health have been the focus of attention for many years; some reviews can be found in [109][110][111][112][113][114][115][116]. Infrastructures and mitigation methods were studied, among others, in [117][118][119][120][121][122][123][124][125][126][127][128]. Finally, the reduction of noise produced by engines has been studied in [129][130][131][132][133][134][135][136][137].…”
Section: Aircraftmentioning
confidence: 99%
“…After the publication of European Noise Directive 2002/49/EC (END) [21], sustainability has grown towards the noise sources required by END: road and railway traffic [22][23][24], airports [25,26], and wind turbines [27,28]. For these type of noise sources, the scientific community has put a lot of effort into developing innovative and environmentally-friendly mitigations, such as low-noise pavements [29,30], live and integrated monitoring systems [31,32], sustainable metamaterial absorber [33,34], and sonic crystal noise barriers made of recycled materials [35].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of noise generation mechanisms is vital for improving mitigation actions [27] applied to the two main actors in the phenomenon: Tires have been optimized [28], and mostly, low noise pavements have recently spread, some of which have even been developed with recycled materials [29,30]. Since tire/road noise depends on structural parameters of road surfaces [31], the European Union has recently prescribed acoustic tests of newly laid surfaces [32] by means of the Close Proximity Index (CPX) method [33] during the first three months from laying date.…”
Section: Introductionmentioning
confidence: 99%